TERAPI PERILAKU BULLYING PERSPEKTIF AL QUR’AN DALAM SURAT ALHUJURAT - Yiying, Yiying; Irman, Irman; Zaini, Hasan (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2024)
Regulations regarding the prohibition of Bullying have been stated in the Al-Qur'an QS. Alhujurat verses 11-12 which have occurred since the prophetic era, but looking at the current situation as the times progress, this bullyi ng behavior is increasingly widespread and has become something that is considered commonplace. for students at school, this is due to a lack of students' understanding of the moral values contained in the Qur'an. This study aims to 1) find out the expression of the lafaẓ of bullying behavior in the Qur'an 2) interpretation of the verses of the Qur'an and hadith on bullying behavior, the approach used in this study is a qualitative approach, while the method used is descriptive analysis method with This type of literature is by collecting data that is related to the researcher's discussion. Based on the results of this research analysis, it shows that the educational implications of QS.Al-hujurat verses 11-12, 1) Prohibition not to make fun of other people, 2) Commands not to self-deprecate and call others with bad titles, 3) Prohibition not to su'udzaan (prejudice), 4) Command not to backbite (backbiting) against fellow Muslims.